Near‐infrared spectroscopy reveals neural perception of vocal emotions in human neonates - Zhang, Dandan (Hum Brain Mapp, 2019)
Processing affective prosody, that is the emotional tone of a speaker, is fundamental to human communication and adaptive behaviors. Previous studies have mainly focused on adults and infants; thus the neural mechanisms underlying the processing of affective prosody in newborns remain unclear. Here, we used near‐infrared spectroscopy to examine the ability of 0‐to‐4‐day‐old neonates to discriminate emotions conveyed by speech prosody in their maternal language and a foreign language. Happy, fearful, and angry prosodies enhanced neural activation in the right superior temporal gyrus relative to neutral prosody in the maternal but not the foreign language. Happy prosody elicited greater activation than negative prosody in the left superior frontal gyrus and the left angular gyrus, regions that have not been associated with affective prosody processing in infants or adults. These findings suggest that sensitivity to affective prosody is formed through prenatal exposure to vocal stimuli of the maternal language. Furthermore, the sensitive neural correlates appeared more distributed in neonates than infants, indicating a high‐level of neural specialization between the neonatal stage and early infancy. Finally, neonates showed preferential neural responses to positive over negative prosody, which is contrary to the “negativity bias” phenomenon established in adult and infant studies.